Revitalization of Sentul Market: Marketing Strategy of Sentul Market Culinary Plaza to Increase Tourist Interest - Wahyunintyas, Yunita Fitri (The Eastasouth Management and Business, 2025)
A number of traditional markets or people's markets in Yogyakarta have begun to be laid out and beautified so that they are more modern and representative for trade activities using the support of the Special Fund (Danais). The presence of the Culinary Plaza in Sentul Market is a new culinary center, most of which is the relocation of street vendors (PKL) from Sewandanan Pakualaman Square. Because its existence is still new, it is very necessary to have a strategy so that the construction of the Culinary Plaza can be used optimally. The research method uses a type of qualitative research that is descriptive with a SWOT analysis approach. SWOT analysis with a qualitative approach, consisting of Strengths, Weaknesses, Opportunities and Threats. The SWOT analysis aims to maximize strengths and opportunities, but can minimize weaknesses and threats to help formulate the right marketing strategy in accordance with the internal environmental conditions and external environmental conditions of the Sentul Market Culinary Plaza.